Teacher Education for National Development Using Google Meet: Issues and Prospects - Fadele Ayotunde Alaba; Adejo Omoka Lucy; Haruna Muhammad Jumare; Madu Ifeyinwa Marisa (Journal of Technology Innovations and Energy, 2024)
This research examines the role of teacher education in Nigeria’s national development using Google Meet, a virtual learning platform. The study assesses the effectiveness of Google Meet in enhancing educators’ professional development and impacting student learning outcomes. It also investigates the challenges and limitations of implementing virtual teacher training in Nigeria. The findings show that Google Meet can improve education quality and foster professional growth. However, internet connectivity and digital infrastructure challenges hinder widespread adoption, especially in rural areas. The research proposes recommendations for optimizing Google Meet in teacher education, such as providing equitable access to digital resources, investing in robust internet connectivity, and implementing ongoing training for educators. This study offers insights for education policymakers and institutions in Nigeria and other developing countries seeking to leverage technology for teacher education and national development. Aligning teacher training with digital innovations can enhance educational outcomes, foster sustainable development, and prepare citizens for a rapidly evolving global landscape